Peningkatan Hasil Belajar Siswa Dalam Pembelajaran Tematik Terpadu Dengan Menggunakan Strategi Mind Mapping Kelas V SD - Rahmayetti, Fitria; Miaz, Yalvema (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
This research purpose is to know increase the learning outcomes in integrated thematic used strateghy Mind Mapping in grades V elementary school. This research is as a Classroom Action Research (CAR) which acted for two cycles. Each cycle consists of the step of Planning, Actuating, Observing, and Reflecting. The subjects of this  research is student V Elementary School 19 ATTS Bukittinggi as many as 19 students. The sources of data are collected from the teacher and the student. The main data collection technique used are observation, tes and non tes. Data analysis used are qualitative and quantitative  data analysis. The result of this research showed that used strateghy Mind Mapping can increase the learning outcomes in integrated thematic student of V Elementary School 19 ATTS Bukittinggi.